Relative Contributions of Complications and Failure to Rescue on Mortality in Older Patients Undergoing Pancreatectomy. Issue 2 (February 2016) - Tamirisa, Nina P.; Parmar, Abhishek D.; Vargas, Gabriela M.; Mehta, Hemalkumar B.; Kilbane, E. Molly; Hall, Bruce L.; Pitt, Henry A.; Riall, Taylor S.
Abstract : Background: For pancreatectomy patients, mortality increases with increasing age. Our study evaluated the relative contribution of overall postoperative complications and failure to rescue rates on the observed increased mortality in older patients undergoing pancreatic resection at specialized centers. Methods: We identified 2694 patients who underwent pancreatic resection from the American College of Surgeons' National Surgical Quality Improvement Pancreatectomy Demonstration Project at 37 high-volume centers. Overall morbidity and in-hospital mortality were determined in patients younger than 80 years (N = 2496) and 80 years or older (N = 198). Failure to rescue was the number of deaths in patients with complications divided by the total number of patients with postoperative complications. Results: No significant differences were observed between patients younger than 80 years and those 80 years or older in the rates of overall complications (41.4% vs 39.4%, P = 0.58). In-hospital mortality increased in patients 80 years or older compared to patients younger than 80 years (3.0% vs 1.1%, P = 0.02). Failures to rescue rates were higher in patients 80 years or older (7.7% vs 2.7%, P = 0.01). Across 37 high-volume centers, unadjusted complication rates ranged from 25.0% to 72.2% and failure to rescue rates ranged from 0.0% to 25.0%. Among patients with postoperative complications, comorbidities associated with failure to rescue were ascites, chronic obstructive pulmonary disease, and diabetes. Complications associated with failure to rescue included acute renal failure, septic shock, and postoperative pulmonary complications. Conclusions: In experienced hands, the rates of complications after pancreatectomy in patients 80 years or older compared to patients younger than 80 years were similar. However, when complications occurred, older patients were more likely to die. Interventions to identify and aggressively treat complications are necessary to decrease mortality in vulnerable older patients.